Headaches after traumatic spinal cord injury in Estonia. (April 2016) - Sabre, Liis; Rugo, Mariann; Asser, Toomas; Kõrv, Janika; Braschinsky, Mark
Background: Patients with traumatic spinal cord injury (TSCI) often suffer from different types of pain. However, headaches after TSCI have not been studied. Aim: The aim of this article is to examine the occurrence of headache among patients with TSCI. Methods: This cross-sectional study included individuals with TSCI from 1997 to 2012 in Estonia. Patients with TSCI were interviewed via telephone. The interview was based on a questionnaire specifically designed to identify headache type using the International Classification of Headache Disorders, third edition (beta version). Results: There were 73 patients with a mean age 37.1 ± 10.6 years. The mean time since TSCI was 7.5 ± 4.0 years. The most frequently mentioned pain was headache (71%), followed by back pain (60%) and pain in neck (44%). Headaches were more frequent after the trauma compared with the headaches before TSCI (71% vs 51%, p = 0.02). Headaches that arose after TSCI were not related to the concomitant brain injury ( p = 0.15). The occurrence of headache did not depend on the severity or the level of the TSCI. Eighty-five percent of patients had not contacted any physician and headache was not diagnosed. Conclusions: This is the first study that evidentially shows that headache is the most prevalent pain condition after TSCI. Despite this, the majority of patients never consult a physician, nor is their headache diagnosed or appropriately managed. This indicates that further studies are needed to provide evidence regarding the prevalence and causes of headache and its impact on quality of life.